(untitled) (Annual of the Faculty of Philosophy in Skopje, 2025)
In 1785 Kant only requested that we must “respect every living being in principle as a purpose in itself and, if possible”, (to) “treat it as such!”. While the “Sanctity of the Moral Law” was the basis for Kant’s Categorical Imperative, for Fritz Jahr’s Bioethical Imperative, it was “Sanctity of Life”, i.e. compassion with all forms of life and living together. Having or not, this in mind, this theoretical base for bioethical reflection, in 1971 (when the name and practice of bioethics appears in the world), our prof. Pavao Vuk-Pavlovic, in his last university lecture, left the students of the Faculty of Philosophy in Skopje the legacy to: “Take care of the living and create loving: Love the life!”. And with this, the seeds for academic investigations and researches about bioethical sensitiveness and around bioethics were sowed, but not recognized and undeveloped in that time. From today’s perspective, unlike many neighboring countries on the Balkan, in Macedonia we doesn’t talk about bioethics as a developed discipline or as a part of scientific activities and research, or even less, bioethics as something that is a systematic part of education, including bioethical education, up ‘till, at least, the last ten to fifteen years, and still with enormous difficulties and obstacles. Do we have any kind of trace in term of history of the bioethical discovering efforts in the meanwhile from 1971 or earlier? Even more, what kind of future do we have for the next generations and the same future generation? What happened in Macedonia with the Jahr’s legacy and his bioethical imperative?